Knowledge regarding diabetes mellitus amongst arts, science and commerce college students of Latur city, Maharashtra - Gaikwad, Bhaskar; Bhalge, Udaykiran; Kulkarani, Pramod; Takalkar, Anant; Sagare, Sunil; Bhise, Mukund (International Journal Of Community Medicine And Public Health, 2019)
Background: Nearly 35 million people are suffering from diabetes in India. The present trend in diabetes is escalating diabetes prevalence and earlier onset of type 2 diabetes in the adult population. Awareness is an important factor in the early diagnosis, adequate treatment and prevention of complications due to diabetes. This study was undertaken to assess the knowledge regarding different aspects of diabetes mellitus among college students. Methods: A cross-sectional study was undertaken with 348 college students of Latur City. The students were administered a 41 items, pre-tested, semi structured questionnaire assessing general and specific knowledge of diabetes like symptoms, causation, risk factors, complication, treatment, attitudes towards people with diabetes etc. The results were analyzed using Microsoft Excel software. Results: Excessive tiredness, non healing wounds, excessive sweating and hunger were mentioned as symptoms of diabetes by 82.47, 73.85% and 72.70% subjects respectively. About (57.76%) study participants were aware of diabetes as a rising problem and only (8.33%) students had correct knowledge of the prevalence. Only (27.30%) were aware that genetic factors are reason for the causation of diabetes. As much as 85.91% subjects stated that blood and urine tests are done for diagnosing diabetic persons. Common complications not identified by the study subjects were impotence (68.39%), stroke (64.65%), ulcer on foot (54.31%), and repeated skin infections (53.16%). Conclusions: Specific knowledge about diabetes is poor among the degree college students, hence appropriate activities to increase awareness about diabetes is the need of the hour.